An accurate and inexpensive color‐based assay for detecting severe anemia in a limited‐resource setting. Issue 12 (12th October 2015) - McGann, Patrick T.; Tyburski, Erika A.; de Oliveira, Vysolela; Santos, Brigida; Ware, Russell E.; Lam, Wilbur A.
Abstract : Severe anemia is an important cause of morbidity and mortality among children in resource‐poor settings, but laboratory diagnostics are often limited in these locations. To address this need, we developed a simple, inexpensive, and color‐based point‐of‐care (POC) assay to detect severe anemia. The purpose of this study was to evaluate the accuracy of this novel POC assay to detect moderate and severe anemia in a limited‐resource setting. The study was a cross‐sectional study conducted on children with sickle cell anemia in Luanda, Angola. The hemoglobin concentrations obtained by the POC assay were compared to reference values measured by a calibrated automated hematology analyzer. A total of 86 samples were analyzed (mean hemoglobin concentration 6.6 g/dL). There was a strong correlation between the hemoglobin concentrations obtained by the POC assay and reference values obtained from an automated hematology analyzer (r=0.88, P <0.0001). The POC assay demonstrated excellent reproducibility (r=0.93, P< 0.0001) and the reagents appeared to be durable in a tropical setting (r=0.93, P< 0.0001). For the detection of severe anemia that may require blood transfusion (hemoglobin <5 g/dL), the POC assay had sensitivity of 88.9% and specificity of 98.7%. These data demonstrate that an inexpensive (<$0.25 USD) POC assay accurately estimates low hemoglobin concentrations and has the potential to become a transformational diagnostic tool for severe anemia in limited‐resource settings. Am. J. Hematol. 90:1122–1127, 2015. © 2015 Wiley Periodicals, Inc.